First identification of rare-earth oxide nucleation in chalcogenide glasses and implications for fabrication of mid-infrared active fibers - Tang, Zhuoqi; Furniss, David; Fay, Michael; Neate, Nigel C.; Cheng, Yin; Barney, Emma; Sojka, Lukasz; Sujecki, S.; Benson, Trevor M.; Seddon, Angela B. (Wiley, 2014)
Gallium (Ga) helps solubilize rare-earth ions in chalcogenide glasses, but has been found to form the dominant crystallizing selenide phase in bulk glass in our previous work. Here, the crystallization behavior is compared of as-annealed 0–3000 ppmw Dy3+-doped Ge–As–Ga–Se glasses with different Ga levels: Ge16.5As(19−x)GaxSe64.5 (at.%), for x = 3 and 10, named Ga3 and Ga10 glass series, respectively. X-ray diffraction and high-resolution transmission electron microscopy are employed to examine crystals in the bulk of the as-prepared glasses, and the crystalline phase is proved to be the same: Ge-modified, face centered cubic α-Ga2Se3. Light scattering of polished glass samples is monitored using Fourier transform spectroscopy. When Ga is decreased from 10 to 3 at.%, the bulk crystallization is dramatically reduced and the optical scattering loss decreases. Surface defects, with a rough topology observed for both series of as-prepared chalcogenide glasses, are demonstrated to comprise Dy, Si, and [O]. For the first time, evidence for the proposed nucleation agent Dy2O3 is found inside the bulk of as-prepared glass. This is an important result because rare-earth ions bound in a high phonon–energy oxide local environment are, as a consequence, inactive mid-infrared fluorophores because they undergo preferential nonradiative decay of excited states.